Heterogeneous R&D spillovers and sustainable growth: Limits to efficient regulation - Anton Bondarev (University of Basel, Center of Business and Economics (WWZ), 2018)
This paper introduces heterogeneity of cross-technologies interactions into the double-differentiated R&D-based endogenous growth model. In this model new technologies appear continuously and older are outdated generating structural change. All technologies may interact with each other through knowledge spillovers which are technology-specific and this results in innovations' heterogeneity. The conditions on the shape of these interactions for the existence of the (sustained) growth path in the decentralized economy as well as for the social planner's problem are established. Next the necessity for government interventions depending on the complexity of these interactions is studied. At last the scale and duration of interventions are demonstrated to be functions of spectral properties of the interactions operator.
Keywords: C61; O32; O38; O41; H3; 330; endogenous structural change; endogenous growth; technological spillovers; R&D policy; government regulation; dynamic stability; spectral theory; optimal control